2018
DOI: 10.4155/fsoa-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Further Axillary Dissection in Breast Cancer Patients with Micrometastases & the Number of Micrometastases: a SEER Population-Based Analysis

Abstract: Aim:To investigate the benefits of axillary dissection in patients with micrometastases.Methods:A review of data from the Surveillance, Epidemiology, and End Results database was performed from 2004 to 2013. Kaplan–Meier curves, Cox regression models, and propensity score matching were utilized to comprehensively evaluate the cohort.Results:Multivariate analysis after propensity score matching showed that patients with one to two micrometastases did not substantially benefit from axillary lymph node dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…After PSM, the differences that existed in the original cohort no longer emerged, thus allowing our results to objectively reflect the differences between the two groups more accurately. After the PSM procedure, the results of our Kaplan-Meier curve analysis showed that further axillary lymph node dissection did not provide longer OS or BCSS compared to sentinel lymph node biopsy only, and this finding is consistent with many previous papers on breast cancer patients with micrometastases ( 9 , 31 34 ). According to the results of several clinical trials, further axillary dissection has been abandoned for breast-conserving patients with SLN micrometastases in some centers ( 31 , 35 ), but it has not been fully analyzed in patients who have undergone mastectomy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…After PSM, the differences that existed in the original cohort no longer emerged, thus allowing our results to objectively reflect the differences between the two groups more accurately. After the PSM procedure, the results of our Kaplan-Meier curve analysis showed that further axillary lymph node dissection did not provide longer OS or BCSS compared to sentinel lymph node biopsy only, and this finding is consistent with many previous papers on breast cancer patients with micrometastases ( 9 , 31 34 ). According to the results of several clinical trials, further axillary dissection has been abandoned for breast-conserving patients with SLN micrometastases in some centers ( 31 , 35 ), but it has not been fully analyzed in patients who have undergone mastectomy.…”
Section: Discussionsupporting
confidence: 91%
“…After stratifying the patients by characteristics, we found that having an age at diagnosis of 50 years or older, being unmarried, having ER-negative status, PR-negative status, or HER2-negative status, and not receiving systemic chemotherapy were all unfavorable independent factors for the prognosis of patients with micrometastases. Previous studies have also come to the same conclusion, and many studies have highlighted the importance of adjuvant systemic therapy for patients with micrometastases ( 7 , 9 , 39 , 40 ). In this study we found that patients in the SLNB with complete ALND group tended to have received chemotherapy.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations